Energy Efficient Data Transfer In Mobile Wireless Sensor Network (International Journal of Engineering and Computer Science, 2015)
The proposed cross-layer operation model is implemented to improve the energy consumption and system throughput of IEEE 802.15.4 Mobile Wireless Sensor Network (MWSN). The proposed model integrates four layers in the network operation: 1) application is used for node location; 2) network is designed to construct the route routing; 3) medium access control used for message forwarding; and 4) physical layers. The location of the mobile nodes is embedded in the routing operation after the route discovery process. The location information is then utilized by the MAC layer transmission power control to adjust the transmission range of the node. This is used to minimize the power utilized by the network interface to reduce the energy consumption of the node(s). The model employs a mechanism to minimize the neighbor discovery broadcasts to the active routes only. Reducing control packet broadcasts between the nodes reduces the network’s consumed energy. It also decreases the occupation period of the wireless channel. The model operation leads the network to consume less energy while maintaining the network packet delivery ratio.